The Classic: Details to the Portrait (In Celebration of the 85th Birthday of V.P. Zinchenko) - Mazilov, V.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2016)
This paper is dedicated to the 85th birthday of Vladmir Zinchenko (1931—2014), a prominent Russian psychologist and philosopher. It traces the main periods in the life of the scientist and attempts to reveal his personal features that shaped the style of his thinking. It is argued that Zinchenko’s most important contribution to psychological science is methodology (even though his contributions reasonably and undoubtedly involve child psychology, engineering psychology, cognitive psychology, as well as poetic anthropology which he himself established), which is due to the fact that Vladimir Zinchenko’s personality and intelligence were principally that of a philosopher in psychology and made him a methodologist and historian of psychology all in one. The paper also stresses the encyclopedic nature of knowledge and broad- ness of views in Vladimir Zinchenko, the diversity and multi-sidedness of his interests. As it is showed, his works embrace and to a great extent implement the main research pattern suggested by the great honored companions, that is, the future pattern of a synthesis of art and science. The paper concludes that Vladimir Zinchenko himself remains our honored companion and that his works reveal to us their messages of wisdom so distinctive of the classic of psychological science. Статья посвящена юбилею выдающегося отечественного психолога, философа, мыслителя В.П. Зинченко (1931—2014). Прослеживается жизненный путь, дается анализ основных этапов деятельности ученого. Предпринимается попытка выделить личностные черты классика психологической науки, характеризующие стиль его мышления и творчества. В статье отстаивается позиция, согласно которой главным вкладом В.П. Зинченко в психологическую науку (хотя исследователь, несомненно и по полному праву, «принадлежит» и детской психологии, и инженерной, и когнитивной, и даже созданной им самим поэтической антропологии) является методология, потому что Владимир Петрович Зинченко был по складу своего интеллекта и личности в первую очередь философом психологии, т. е. методологом и историком психологии в одном лице. Подчеркиваются энциклопедизм и широта взглядов В.П. Зинченко, разносторонность и разнообразие его интересов. Показано, что в работах ученого обозначена и в значительной степени реализована магистральная линия исследований, подсказанная великими Заслуженными собеседниками, линия на достижение в будущем синтеза наук и искусств. Утверждается, что В.П. Зинченко остается нашим заслуженным собеседником, в работах которого мы по-прежнему находим подсказки, несущие печать мудрости, столь свойственной классику психологической науки.